Synthesis of magnetoliposomes and evaluating of their cell internalization by external magnetic field - Lin, Jinjie (2014)
While thermosensitive liposomes and magnetic nanoparticles are widely researched on by many pharmaceutical companies, magnetoliposomes show higher efficiency of triggering liposomal release at inner organs, than conventional ones. Thus, this project aims to develop a magnetic-sensitive drug delivery system, coupled to widely used nanoparticles and liposomes, which could be adopted by these companies. Lysolipid (MPPC)-containing thermosensitive long circulating liposomes were synthesized from different formulations. The size and volume, and site of encapsulation, of magnetite (Fe3O4) nanoparticles entrapped, were varied. The thermal stability, and cytotoxicity effect on B16-F10 melanoma cell line, of the magnetoliposomes were studied. The size (hydrodynamic diameter) of the magnetoliposomes generally ranged from 100nm to 200nm, and showed high stability. Encapsulation of larger and lower volume of nanoparticles, within the liposomes’ cores, led to smaller magnetoliposomes. At 42oC and 48oC, the liposomal release efficiencies were high (76% and 100%, respectively). 1μl of magnetoliposomes/ml media resulted in low cytotoxicity (64.9% of cells remained viable).